Unzipping Lemuria from its Himalaya suture to understand mammalian origins - de Wit, Maarten J; Masters, Judith (Himalayan Journal of Sciences, 2008)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--> <!--[if gte mso 10]> <![endif]--> DOI = 10.3126/hjs.v5i7.1249 Himalayan Journal of Sciences Vol.5(7) (Special Issue) 2008 p.44